Interdisciplinary research in technology and management : proceedings of the International Conference on Interdisciplinary Research in Technology and Management (IRTM, 2022), 24-26 February 2022, Kolkata, India /: proceedings of the International Conference on Interdisciplinary Research in Technology and Management (IRTM, 2022), 24-26 February 2022, Kolkata, India. (2023) - Unknown
No abstract available